KHẢ NĂNG HẤP PHỤ PHẨM MÀU ALIZARIN VÀNG G CỦA VẬT LIỆU COMPOZIT TỪ TÍNH Fe3O4 NANO/CACBON HOẠT TÍNH - Thái, Bùi Thị; Hoàn, Nguyễn Xuân (Vietnam Journal of Chemistry, 2012)
Magnetic Fe3O4/activated carbon composite have been prepared by hydrothermal reaction with homogeneous morphology. The value of saturation magnetization MS > 10 emu/g was obtained. Langmuir isotherm model was used to investigate the adsoprtion of Alizarin yellow-G dye on Fe3O4/activated carbon composite. Results showed that the maximum adsorption capacities qmax were higher than 350 mg/g.